A 980nm Diode Laser Clot Formation of the Rabbit’s Dental Sockets after Teeth Extraction - Mirdan, Balsam M. (Iraqi Journal of Laser, 2019)
The aim of this research work is to evaluate the use of 980 nm diode laser in clotting the bloodin the bone socket after tooth extraction. The objective is to prevent possible clot dislodgement which isa defect that may lead to possible infection. A number of rabbits were irradiated using 980nm CW modediode laser, 0.86W power output for 9s and 15s exposure time. The irradiated groups were studiedhistopathologically in comparison with a control group. Results showed that laser photothermalcoagulation was of benefit in minimizing the possibility of the incidence of postoperative complications.The formation of the clot reduces the possibility of bleeding and infection.